MITOS DI KAMPUNG PULO DAN CANDI CANGKUANG KECAMATAN LELES KABUPATEN GARUT - enoh Enoh (Jurnal Budaya Etnika, 2018)
ABSTRACT The Pulo’s village, is a custom’s village, place at Leles district, Garut regent’s, as a culture pledge tourism destination, have many uniqueness and special mythology, must obedient by his resident also by visitors. Is custom’s village can for a culture lab who appreciated his local genius value used for large society?Using short survey and limited supervision, and interview, got the result, truly the result was writed by researcher and surveyer before. Difference with visite the student and lecturer of ISBI Bandung, in mereover action basicly on the culture theories about custom village and his mythology.The result is Pulo’s village as a custom village, have some tradisional and mythology melted with paith as muslims, so that became syncretism between tradisional dan religi. Among bumpy mythologies is don’t visit wednesday; don’t have an affair with in pledge location; costum house don’t more six houses and one mosque; don’t take care of big animals four’s leg; don’t play on the goong. Beside invention about mithology, we are also see many people pray in front of the holy grave Lord Arief Muhammad who faithed full of mercy and holiness, of course all desire on the heart will be accepted. The collision on mithology will bring disaster, according to the testimony became real, among other things, tornados, suddenly rain and lightning, etc. Thing that can so as right or just right, like that according to Mr. Zaki Munawar as an officer in charge culture pledge at Pulo’s village. Keywords: Cangkuang, Myth, Sincretic.  ABSTRAK Kampung Pulo adalah kampung adat, berlokasi di kecamatan Leles, kabupaten Garut adalah destinasi wisata cagar budaya yang memiliki keunikan dan mitos tersendiri, yang harus ditaati oleh penduduk setempat juga harus diikuti oleh para pengunjung. Apakah kampung adat dapat dijadikan lab budaya yang dapat diapresiasi nilai-nilai kearifan lokalnya sehingga dapat dihayati dan dimanfaatkan untuk masyarakat yang lebih luas? Melalui survey singkat dan pengamatan terbatas, serta wawancara, maka diperoleh hasil, yang sesungguhnya hasil ini sudah banyak ditulis oleh para peneliti dan pengamat terdahulu. Perbedaan dengan kunjungan mahasiswa dan dosen antropologi budaya ISBI Bandung terletak pada tindakan kajian lebih lanjut berdasar teori-teori budaya tentang kampung adat dan mitologinya.Hasilnya adalah Kampung Pulo sebagai kampung Adat memiliki beberapa tradisi dan mitos yang larut dengan kepercayaan sekarang sebagai pemeluk agama Islam, sehingga terjadi semacam sinkretik antara tradisi dan agama. Di antara mitos yang menonjol antara lain: jangan berkunjung pada hari rabu; jangan berpacaran di lokasi cagar, rumah adat tidak boleh lebih dari enam rumah dan satu mesjid, jangan memelihara hewan besar berkaki empat, jangan menabuh goong. Di samping temuan tentang mitos, tersaksikan pula banyak pengunjung berdoa di depan makam Embah Dalem Arief Muhammad yang diyakini penuh barokah dan karomah, niscaya segala keinginan yang diangankan bakal terkabul.Pelanggaran terhadap mitos bisa membawa bencana, yang konon sudah terbukti antara lain, ada angin ribut, tiba-tiba hujan-petir, tiba-tiba putus cinta, dan sebagainya. Hal itu bisa jadi ‘kebetulan’ atau bisa jadi ‘betulan’ demikian menurut Zaki Munawar petugas di cagar budaya Kampung Pulo. Kata Kunci: Cangkuang, Mitos, Sinkretis